Searching to improve learning from complex animated basketball scenes: when decreasing the presentation speed is more efficient than using segmentation. Issue 3 (27th May 2021) - Rekik, Ghazi; Belkhir, Yosra; Jarraya, Mohamed
ABSTRACT: In two separate experiments, the authors investigated how a complex animated basketball scene should be designed in order to avoid the high cognitive load due to the transient nature of information. Using system-paced segments and decreasing the video's presentation speed were tested as instructional strategies to reduce students' cognitive load. The effectiveness of continuous versus segmented videos was explored in the first experiment. The second experiment compared the effectiveness of normal versus low levels of presentation speed. The results indicated that while the segmentation strategy has no significant effect on learning outcomes, students profited more from the low than the normal presentation speed, as evidenced by the more favourable relationship between mental effort investment and game performance. These findings suggest that decreasing the presentation speed is an efficient instructional strategy that helps to improve learning from complex animated basketball scenes.